Approaches to ultra-low radiation dose coronary artery calcium scoring based on 3rd generation dual-source CT: A phantom study. Issue 1 (January 2016) - McQuiston, Andrew D.; Muscogiuri, Giuseppe; Schoepf, U. Joseph; Meinel, Felix G.; Canstein, Christian; Varga-Szemes, Akos; Cannao', Paola M.; Wichmann, Julian L.; Allmendinger, Thomas; Vliegenthart, Rozemarijn; De Cecco, Carlo N.
Highlights: Calcium scoring is becoming increasingly important for cardiac risk stratification. 3rd generation dual-source CT can substantially decrease radiation exposure. Sn100 kV scanning may allow for accurate quantification of calcium score. Abstract: Objectives: To investigate to what extent 3rd generation dual-source computed tomography (DSCT) can reduce radiation dose in coronary artery calcium scoring. Methods: Image acquisition was performed using a stationary calcification phantom. Prospectively electrocardiogram (ECG)-triggered 120 kV sequential, and 120 and Sn100 kV ultra-high pitch (UHP) acquisitions were performed with different tube currents (80, 60, 40, 20 mA). Images were reconstructed using filtered back projection (FBP) and 3rd generation iterative reconstruction (IR). Contrast-to-noise ratio (CNR), Agatston score, calcium volume, and radiation dose were assessed. For statistical analysis Friedman tests and Wilcoxon rank sum tests were used. Results: Even at reduced tube currents, the three acquisition techniques did not show significant differences in Agatston score ( p = 0.4) or calcium volume ( p = 0.08) with FBP reconstruction. Calcium volumes were significantly lower for 3rd generation IR compared to FBP reconstructions ( p < 0.01). CTDIvol for the 120 kV sequential, 120 and Sn100 kV UHP acquisitions at 80 and 20 mA were 1.2–0.37, 0.48–0.17, and 0.07–0.02 mGy, respectively. Conclusion: 3rd generation DSCT enabled a reduction of tube current in both the sequential and UHP acquisitions without significantly affecting coronary calcium scoring. Tin filtered 100 kV scanning may allow accurate quantification of calcium score without correction of the HU threshold.